Comparative study of anthropometric measurement and body composition between junior handball and basketball players from the Serbian national league - B.D. Masanovic; T.T. Bavcevic; I.A. Prskalo (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Background and Study Aim: The purpose of this study was to describe anthropometric characteristics and body composition of junior handball and basketball players from the Serbian National League, as well as to make a comparison between them. Material and Methods: Sixty male athletes were enrolled in the study and they were divided into three groups: fifteen handball players, thirteen basketball players and thirty-two healthy sedentary subjects. All subjects were assessed for the anthropometric measures required for calculation of body composition variables, using standardized procedures recommended by previous studies. Data were analyzed using SPSS software and descriptive statistics was expressed as a mean (SD) for each variable, while the ANOVA and LSD Post Hoc tests were carried out to detect the effects of each type of sport. Results: The results showed there was no significant difference in body weight, body mass index or in bone content, while a significant difference was found in body height as well as in muscle mass and body fat. Conclusions: These findings may give coaches from the region better working knowledge, and suggest to them to follow recent methods of selection techniques and to be more careful during the process of talent identification.